Survivin isoforms and clinicopathological characteristics in colorectal adenocarcinomas using real-time qPCR - Pavlidou, A.; Dalamaga, M; Kroupis, C.; Konstantoudakis, G.; Belimezi, M.; Athanasas, G.; Dimas, K. (World J.Gastroenterol., 2011)
AIM: To investigate three isoforms of survivin in colorectal adenocarcinomas. METHODS: We used the LightCycler Technology (Roche), along with a common forward primer and reverse primers specific for the splice variants and two common hybridization probes labeled with fluorescein and LightCycler-Red fluorophore (LC-Red 640). Real time quantitative polymerase chain reaction (PCR) was performed on cDNAs from 52 tumor specimens from colorectal cancer patients and 10 unrelated normal colorectal tissues. In the patients group, carcinoembryonic antigen (CEA) and CA19-9 tumor markers were also measured immunochemically. RESULTS: Wild type survivin mRNA isoform was expressed in 48% of the 52 tumor samples, survivin-2b in 38% and survivin-DeltaEpsilonx3 in 29%, while no expression was found in normal tissues. The mRNA expression of wild type survivin presented a significant correlation with the expression of the ratio of survivin-2b, survivin-DeltaEpsilonx3, survivin-2b/wild type survivin and survivin-DeltaEpsilonx3/wild type survivin (P < 0.001). The mRNA expression of wild-survivin and survivin-DeltaEpsilonx3 was related with tumor size and invasion (P = 0.006 and P < 0.005, respectively). A significant difference was found between survivin-2b and morphologic cancer type. Also, the ratio of survivin-DeltaEx3/wild-survivin was significantly associated with prognosis. No association was observed between the three isoforms and grade, metastasis, Dukes stage and gender. The three isoforms were not correlated with CEA and CA19-9. CONCLUSION: Survivin isoforms may play a role in cell apoptosis and their quantification could provide information about clinical management of patients suffering from colorectal cancer
Keywords: Adenocarcinoma; Adult; Aged; Aged,80 and over; analysis; Analysis of Variance; apoptosis; CA-19-9 Antigen; Carcinoembryonic antigen; Case-Control Studies; Chi-Square Distribution; Colorectal Neoplasms; Female; genetics; Greece; Humans; Immunohistochemistry; immunology; Inhibitor of Apoptosis Proteins; Kaplan-Meier Estimate; Male; Middle Aged; mortality; Neoplasm Invasiveness; Neoplasm Staging; pathology; polymerase chain reaction; Prognosis; Protein Isoforms; RNA,Messenger; Tumor Burden